PELAKSANAAN SUPERVISI PENDIDIKAN DALAM PENINGKATAN KINERJA GURU DI MADRASAH IBTIDAIYAH AL MAWADDAHWARRAHMAH KOLAKA - Andini; Suhrah; Andi Faisal (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
This study aims to explore the implementation of educational supervision in improving teacher performance at Madrasah Ibtidaiyah Al Mawaddah Warrahmah Kolaka. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving the head of the madrasah and teachers. The results revealed that supervision was carried out through several stages, including planning, classroom observation, data analysis, feedback, and follow-up actions. Despite challenges such as time constraints, limited supervisory skills, and lack of institutional support, educational supervision had a significant impact on enhancing teacher performance, particularly in instructional planning, classroom management, and evaluation practices. The study concludes that effective and consistent supervision contributes to improving the overall quality of education in the madrasah. It is recommended that school leaders strengthen their supervisory roles through training and institutional support.